ACUTE AND SUBCHRONIC TOXICITY STUDIES OF THE CARBONATED DRINK EXTRACT OF ENANTIA CHLORANTHA STEM BARK (FUDMA JOURNAL OF SCIENCES, 2025)
Enantia chlorantha is a plant known for its medicinal properties, particularly in traditional medicine across West Africa. The acute and sub chronic toxicity studies of the extract were evaluated. Group 1 animals were given distilled water while Groups 2 – 4 were administered 50, 150 and 250 mg/kg body weight of the extract respectively. The LD50 values from the acute toxicity study of the extracts were greater than 5000 mg/kg body weight. The RBC, Hb, HCT, MCV, MCH, MCHC, and platelets levels were higher (p > 0.05) in all the extract treated groups. There was no significant difference (p > 0.05) in the serum TC, TG, HDL, LDL, VLDL - cholesterol levels in all the treated groups when compared to the control group. This showed that the extracts did not affect the lipid profile of the mice. There were no significant (p > 0.05) difference in ALP, AST, ALT and GGT activities. The Potassium levels were non-significantly (p > 0.05) higher in the extracts treated groups when compared to the control group. Significant (p < 0.05) increased in GSH concentration was observed in the mice administered 250 mg/kg body weight of the extract when compared with the control group. No prominent hepatocellular or glomerular damages were observed in the vital organs. The findings suggest that the carbonated drink extract of E. chlorantha stem bark is safe for use and therefore supports the traditional use of the plant in treating various disease condition.
Keywords: Toxicity; Carbonated drink; Enantia chlorantha; Liver; Kidney